Lactoferrin impairs pathogen virulence through its proteolytic activity - Ongena, Ruben; Dierick, Matthias; Vanrompay, Daisy; Cox, Eric; Devriendt, Bert (Frontiers in Veterinary Science, 2024)
Antibiotics, often hailed as ‘miracle drugs’ in the 20th century, have revolutionised medicine by saving millions of lives in human and veterinary medicine, effectively combatting bacterial infections. However, the escalating global challenge of antimicrobial resistance and the appearance and spread of multidrug-resistant pathogens necessitates research into alternatives. One such alternative could be lactoferrin. Lactoferrin, an iron-binding multifunctional protein, is abundantly present in mammalian secretions and exhibits antimicrobial and immunomodulatory activities. An often overlooked aspect of lactoferrin is its proteolytic activity, which could contribute to its antibacterial activity. The proteolytic activity of lactoferrin has been linked to the degradation of virulence factors from several bacterial pathogens, impeding their colonisation and potentially limiting their pathogenicity. Despite numerous studies, the exact proteolytically active site of lactoferrin, the specific bacterial virulence factors it degrades and the underlying mechanism remain incompletely understood. This review gives an overview of the current knowledge concerning the proteolytic activity of lactoferrins and summarises the bacterial virulence factors degraded by lactoferrins. We further detail how a deeper understanding of the proteolytic activity of lactoferrin might position it as a viable alternative for antibiotics, being crucial to halt the spread of multi-drug resistant bacteria.